Distribution and speciation of bromine in mammalian tissue and fluids by X-ray fluorescence imaging and X-ray absorption spectroscopy1. Issue 5 (13th May 2015) - Ceko, Melanie J.; Hummitzsch, Katja; Hatzirodos, Nicholas; Bonner, Wendy; James, Simon A.; Kirby, Jason K.; Rodgers, Raymond J.; Harris, Hugh H.
<x xml:space="preserve">Abstract</x> The first study of bromine speciation and distribution in mammalian tissues using X-rays shows bromine present predominantly as bromide.